Two-Step Esitmation of Linear Models with Ordinal Unoberved Variables: The Case of Corporate Bonds - WU, Chunchi (Institutional Knowledge at Singapore Management University, 1990)
This article proposes a two-step method for estimating the impact of bond indenture provisions and other financial variables on the risk and yields of investment-grade and speculative corporate bonds. In the first step, the default risk of bonds is estimated as a function of indenture provisions and the characteristics of bonds and the issuing firms by an ordered probit. In the second step, the effects of default risk and bond characteristics on yields are estimated after a measure of bond default risk is obtained by a conditional-mean method.